Harmonization of Land Regulations and Notary Authority in the Issuance of Building Rights Title Over Management - Asih Wastuti; I Gusti Ketut Ayu Rachmi Handayani; Lego Karjoko (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
The complexity of land regulations in Indonesia, particularly regarding the issuance of Building Rights Title (HGB) over Management Rights (HPL), has created various legal challenges that affect investment certainty and public service efficiency. This study aims to analyze the harmonization of land regulations and notary authority in issuing HGB over HPL, focusing on regulatory overlaps, implementation challenges, and optimization strategies. Using normative legal research methods with a statutory and conceptual approach, this study examines various regulations, academic literature, and empirical data related to land registration processes. The results show that regulatory harmonization has significantly improved legal certainty and service efficiency, reducing land disputes by 45% and shortening the HGB issuance process from 180 to 90 working days. The strengthening of notary institutional capacity and implementation of effective supervision systems has contributed to improved public service quality, achieving an 85% satisfaction rate. This research concludes that harmonization of land regulations and notary authority is crucial for creating a more effective and efficient land law system, positively impacting investment climate and national development.